Evaluación técnico económica y ambiental de la turbina Michell Banki aplicada a una pico central hidroeléctrica en la parroquia San Lucas de la ciudad de Loja. - Fernández Ponce, Roberto Carlos (2012)
To promote the exploitation of water resources on a small scale in an orderly and clean, it is necessary to have previous study guide and serve as basis for new applications that help solve the need for electricity in rural areas because they were removed from the area urban can not enjoy this service. That's why the subject of this research is the study of behavior Michell Banki turbine in the smaller hydroelectric plant (SHP). It starts with collecting all the information necessary for calculation, design, construction and installation of intake, raceway, sand trap, forebay, penstock, turbine, electric generator. It also took into account suggestions from experienced professionals in this field. The civilian uprising picocentral hydro is in the parish of "San Lucas" Loja Canton. After installation is monitoring key parameters such as flow, voltage, current and frequency for three months and the results produced a technical document containing the plan of installation, operation and maintenance of the SHP. For the development of the project necessitated the use of AutoCAD 2011 software to design planes also machine tools and measuring instruments.